Extraction of secondary metabolites, phytochemical screening and the analysis of antibacterial activity in Spirulina platensis - Ferdaaus, Jannaatul (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.